STATENESS IN THEGEOPOLITICAL TURBULENCE - Шаповаленко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
A concept «stateness» is analysed from point of the functional approaches and the functions of the state in the conditions of globalization. Attention on changeability of functions of the state applies in the conditions of the guided international chaos. Reasons of geopolitical turbulence at the beginning XXI century are analyzed too.